(untitled) (diségno, 2020)
Laser scanners and SfM photogrammetry corrupted the secular connection between measure and drawing, based on sketches drafted on site that usually prefigured plans, sections and fronts of the surveyed building. This study aims at stating, through a test on a case study, that digital tools set up new connections between drawing and measure and provide unprecedented opportunities for investigations that address the design of a monument or a work of art. The proposed case study is the reconstruction of the design of the facade of Palazzo Aiutamicristo, built in Palermo in the last decade of the XV century by the caput magister Matteo Carnilivari. The facade was deeply transformed few years later, probably before 1535, when the palace hosted King Charles V visiting Palermo. Traces of the windows and cornices of the original facade survived the transformation; the reconstruction of Carnilivaris’s design, developed on a digital replica of the facade, evidences the strength of the digital connection between drawing and measure; drawing detects connections that allow the reconstruction of an architectural element from a fragment. The detection of the alignment of windows at different levels led to the detection of new traces, new measures and new correspondences.